Alternative Scholarship through Table-top Games: A Practical Demonstration - VanderSchans, Arielle; Mayhew, Alex; Cornwell, Sarah E. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2020)
Research can take many forms, especially in a field as diverse as library studies. This panel will bring together several emerging scholars as they navigate current Library and Information Science issues through the medium of table-top games. It is our hope that this panel will illustrate how alternative scholarship can be used to teach and explore emerging issues in the field of LIS. La recherche peut prendre de nombreuses formes, en particulier dans un domaine aussi divers que la bibliothéconomie. Ce panel réunira plusieurs chercheurs émergents alors qu'ils explorent les enjeux actuels des bibliothèques et des sciences de l'information à travers les jeux de table. Nous espérons que ce panel illustrera comment des méthodes alternatives peuvent être utilisées pour enseigner et explorer les questions émergentes dans le domaine de la bibliothéconomie et des sciences de l'information.